Sox, Fox, and Lmx1b binding sites differentially regulate a Gdf5-Associated regulatory region during elbow development - Yeboah, Ruth-Love; Pira, Charmaine U.; Shankel, Matthew; Cooper, Allen M.; Haro, Endika; Ly, Van-Dai; Wysong, Kenrick; Zhang, Michael; Sandoval, Nicole; Oberg, Kerby C. (Frontiers in Cell and Developmental Biology, 2023)
The articulating ends of limb bones have precise morphology and asymmetry that ensures proper joint function. Growth differentiation factor 5 (Gdf5) is a secreted morphogen involved in cartilage and bone development that contributes to the architecture of developing joints. Dysregulation of Gdf5 results in joint dysmorphogenesis often leading to progressive joint degeneration or osteoarthritis (OA). The transcription factors and cis-regulatory modules (CRMs) that regulate Gdf5 expression are not well characterized. We previously identified a Gdf5-associated regulatory region (GARR) that contains predicted binding sites for Lmx1b, Osr2, Fox, and the Sox transcription factors. These transcription factors are recognized factors involved in joint morphogenesis and skeletal development. Gdf5 expression overlapped the expression of these transcription factors during joint development both by in situ hybridization (ISH) and scRNA-seq analyses. Within the GARR CRM, mutation of two binding sites common to Fox and Sox transcription factors reduced enhancer activity to background levels in micromass cultures and in ovo embryonic chicken wing bioassays, whereas mutation of two Sox-only binding sites caused a significant increase in activity. These results indicate that the Fox/Sox binding sites are required for activity, while the Sox-only sites are involved in repression of activity. Mutation of Lmx1b binding sites in GARR caused an overall reduction in enhancer activity in vitro and a dorsal reduction in ovo. Despite a recognized role for Osr2 in joint development, disruption of the predicted Osr2 site did not alter GARR activity. Taken together, our data indicates that GARR integrates positive, repressive, and asymmetrical inputs to fine-tune the expression of Gdf5 during elbow joint development.